2018
DOI: 10.12691/jfnr-6-10-2
|View full text |Cite
|
Sign up to set email alerts
|

<i>In-vitro </i>Prebiotic Activity of Grape Seed Flour Highly Rich in Flavonoid and Dietary Fiber

Abstract: Interactions between lactic acid bacteria (LAB) and dietary polyphenols are not fully understood. This study determined the prebiotic effects of grape seed flour (GSF, a byproduct of wine making) and their polyphenol extracts (GSE) on the growth of 10 strains of probiotic LAB recently isolated from the kefir and pathogenic Clostridium perfringens. Growth rate of the LAB, Leuconostoc mesenteroides DH 1608, was the highest among 10 strains of LAB when cultivated with GSF. GSE, containing an equivalent amount of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Our study and other previous studies have shown that WGF or grape seed extract stimulates the growth of Lactobacillus spp. and inhibits Clostridium histolyticum. Body and adipose tissue weights were closely related to modulation of the intestinal microbiota in diet-induced obese (DIO) mice fed diets containing WGF . These results suggest that the prebiotic action of WGF can improve obesity and obesity-related diseases.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Our study and other previous studies have shown that WGF or grape seed extract stimulates the growth of Lactobacillus spp. and inhibits Clostridium histolyticum. Body and adipose tissue weights were closely related to modulation of the intestinal microbiota in diet-induced obese (DIO) mice fed diets containing WGF . These results suggest that the prebiotic action of WGF can improve obesity and obesity-related diseases.…”
Section: Introductionmentioning
confidence: 86%
“…Furthermore, we isolated Lactobacillus kefiri DH5 that, when fed to mice, reduced obesity and fatty liver disease by upregulating genes for fatty acid oxidation in adipose tissue, supporting a probiotic role and specific mechanism for this bacterium. Recently, we have shown that WGF stimulates the in vitro growth of L. kefiri DH5, 14 suggesting that the combination of WGF and LAB has potential synbiotic benefits as pre-and probiotics, respectively. Indeed, we reported that the synergistic amelioration of highfat (HF)-induced obesity and metabolic dysfunctions in a study focused on the relationship between physiological biomarkers and gene expression of liver and adipose tissues using a microarray analysis.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To test the biological potential of extracted fiber and the effects of the digestion process, fermentation was performed before and after the in vitro gastrointestinal digestion on selected beneficial host microorganisms according to the methodologies established by [ 27 , 28 , 29 , 30 ]. A 10 mL volume of each homogenized fraction and control were centrifuged at 948× g , 10 min at 4 °C, and the supernatants and pellets were separated.…”
Section: Methodsmentioning
confidence: 99%